2008
DOI: 10.1016/j.eurpsy.2008.01.746
|View full text |Cite
|
Sign up to set email alerts
|

The dimensional structure of the Wisconsin schizotypy scales: Factor identification and construct validity

Abstract: The present study examined the factor structure underlying the Wisconsin Schizotypy Scales and the validity of these dimensions. Confirmatory factor analysis with 6137 nonclinical young adults supported a 2-factor model with positive and negative schizotypy dimensions. As predicted, the schizotypy dimensions were differentially related to psychopathology, personality, and social impairment. Both dimensions were related to schizotypal and paranoid symptoms. Positive schizotypy was uniquely related to psychoticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
113
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(135 citation statements)
references
References 59 publications
20
113
0
2
Order By: Relevance
“…They do not map directly onto DSM-IV-TR symptoms of SPD, but rather follow a characterization of schizotypy proposed by Paul Meehl (1964). Recent factor analyses of these scales showed a two-factor model that emphasizes both positive schizotypy and negative schizotypy (Kwapil et al 2008). …”
Section: Measurement Of Cluster a Personality Disordersmentioning
confidence: 99%
“…They do not map directly onto DSM-IV-TR symptoms of SPD, but rather follow a characterization of schizotypy proposed by Paul Meehl (1964). Recent factor analyses of these scales showed a two-factor model that emphasizes both positive schizotypy and negative schizotypy (Kwapil et al 2008). …”
Section: Measurement Of Cluster a Personality Disordersmentioning
confidence: 99%
“…Studies exploring the dimensional structure of the psychosis proneness scales reported a 2-factor model with positive and negative schizotypy dimensions (e.g., Kelley & Coursey, 1992 ;Kwapil, Barrantes-Vidal, & Silvia, 2008 ). The positive dimension is characterized mainly by magical ideation and perceptual aberration, while the negative dimension is characterized by physical and social anhedonia.…”
mentioning
confidence: 99%
“…For the analyses in this paper, we combined scores of 1 and 2 into one score, 1 (present). The diagnosticians also assigned scores on each of the six dimensions included in the Chapman Psychosis Rating Scale (CPRS): transmission of ones’ own thoughts, passivity experiences, voice and auditory hallucinations, thought withdrawal, aberrant beliefs, and visual experiences (Chapman and Chapman, 1980; Kwapil et al, 1999; Kwapil et al, 2008). …”
Section: Methodsmentioning
confidence: 99%